Reasons for Emigration and Its Consequences for Lithuanian Economy - Rudžinskienė, Rasa; Paulauskaitė, Lina (Socialinė teorija, empirija, politika ir praktika, 2014)
Summary The international emigration process, its reasons and consequences for the Lithuanian economy are analyzed in this article. The concepts of migration, emigration, transmigration have been identified in this article. An analysis of the migration extent has also been done. This analysis has revealed that almost 500 thousand people (evaluated as emigrants who have and have not declared their departure) have gone out from Lithuania during the period 2001–2012. The main emigration destination countries are named in the article. These countries are the United Kingdom, Ireland, Germany, Norway, and Spain. The quantitative research of emigrants is presented in the article in order to characterize the most important reasons for emigration as well as to create the hypothetical portrait of Lithuanian emigrants, which helps to identify the main features of Lithuanian emigrants. Key wors: emigration, Lithuanian people, consequences, economy